2012
DOI: 10.1007/s13197-012-0809-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clarification on physicochemical characteristics, antioxidant capacity and quality attributes of açaí (Euterpe oleracea Mart.) juice

Abstract: The effects of a clarifying process using pectinases and chitosan on the physicochemical characteristics, antioxidant capacity and quality attributes of açaí fruit (Euterpe oleracea Mart.) juice were evaluated. Clarification of acaí pulp resulted (P ≤ 0.05) in a 50 % loss of total anthocyanin (4.2730 mg/100 mL) and 29 % reduction in antioxidant capacity (33.60 μM FeSO4/g). A high association (P ≤ 0.05) was found between the decrease of antioxidant capacity and total anthocyanin loss. The use of pectinases asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 42 publications
0
20
0
1
Order By: Relevance
“…In addition, brown compounds could be adsorbed onto the surface of PVPP molecules, and the complexes settle down, as reported for pomegranate juice (Alper et al ., ). Furthermore, a reduction in the brown colour after clarification with chitosan was reported in acai juice (Cesar et al ., ). During storage, an increase in the BI was observed in all samples as shown in Figure S4 (c).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, brown compounds could be adsorbed onto the surface of PVPP molecules, and the complexes settle down, as reported for pomegranate juice (Alper et al ., ). Furthermore, a reduction in the brown colour after clarification with chitosan was reported in acai juice (Cesar et al ., ). During storage, an increase in the BI was observed in all samples as shown in Figure S4 (c).…”
Section: Resultsmentioning
confidence: 97%
“…Shahidi et al (1999) revealed that chitosan has a good affinity with polyphenol compounds. In addition, Cesar et al (2012) reported that chitosan, as a clarifying agent, interacts with polyphenol inducing flocculation and sedimentation in acai juice. From the results, the bentonite-treated sample had the highest polyphenol content when compared with other clarified samples.…”
Section: Change In Polyphenol Content Of Pasteurised Palmyra Palm Sapmentioning
confidence: 99%
“…In addition, sample added 1.00 g/L chitosan exhibited lower sucrose, fructose and glucose content than those added 0.50 g/L chitosan. The decrease in reducing sugar and total sugar during clarification of juice by using high concentration of chitosan was reported by Cesar et al (2012).…”
Section: Change In Invertase Activity Of Pasteurized Palm Sap Duringmentioning
confidence: 83%
“…This result was probably related to the coagulation properties of chitosan, particularly at high concentration. Cesar et al (2012) also reported that a decrease in TSS was found after clarification of acai juice by using high concentration of chitosan.…”
Section: Change In Lightness and Clarity Of Pasteurized Palm Sap Durimentioning
confidence: 91%
“…The use of these enzymes also enhances the extraction process by making juices more transparent. Using chitosan as a clarifying agent, a commercial pectinolytic enzyme Citrozym‐Ultra L (from A. aculeatus and Aspergillus niger ; Novozymes) showed better results in the production of clear açaí palm juices by reducing the lipids, insoluble solids, and other substances that can produce haze in açaí palm juices (Cesar and others ). In addition, infusion of pectinases and β‐glucosidase activity have also shown better results in altering texture, flavor, and other sensory properties such as aroma and volatile characteristics of fruit and vegetable juices during processing (Kuhad and others ).…”
Section: Applications Of Lignocellulolytic Enzymes In the Fruit And Vmentioning
confidence: 99%